FAKTOR PENYEBAB KESULITAN BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 11 PEKANBARU - Jum’atiska Rois; Sumarno '; Gimin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was aimed to find out the lack of students’ study effects for the eleventh grade students of SMAN 11 Pekanbaru. The population in this research was the eleventh grade students that was totaled 52 students. And the sample in this research was overall of eleventh students of SMAN 11 Pekanbaru. The collecting data used was questionnaire and documentation. The analysis data used was double linier of regression. The result of this research showed that the motivation factor, the teacher pedagogic competency partially influenced significantly for the difficulties of students’ study of the eleventh grade students at SMAN 11 Pekanbaru, and the professional teacher competency was not influenced significantly for the study of students’ difficulties. Based on regression of the coefficient, the motivation effect was -0,973, the teacher pedagogic competency was -0,668 and the professional teacher competency overall was -0,873. The motivation, the pedagogic competency and the professional teacher competency was overall influenced for the difficulties of students’ study, and it was for economic subject class of the eleventh grade students in SMAN 11 Pekanbaru by determining to 47%.Keywords: The difficulties of study, the teacher pedagogic competency, and the professional teacher competency